Mannheimiose atípica em emas (Rhea americana) cativas - Antunes, João Marcelo Azevedo de Paula (2016)
Mannheimia haemolytica (MH) is a major cause of respiratory disease in bovine complex (BRDC) that causes great economic losses. To this day, there are no reports of birds affected by this bacterium. The present report describes an atypical outbreak of mannheimiosis in captive rheas (Rhea americana).